Certain Results on Ricci Solitons in Trans-Sasakian Manifolds. (13th February 2013) - Bagewadi, C. S.; Ingalahalli, Gurupadavva
Abstract : We study and obtain results on Ricci solitons in trans-Sasakian manifolds satisfying R ( ξ, X ) · C ̃ = 0, P ( ξ, X ) · C ̃ = 0, H ( ξ, X ) · S = 0, and C ̃ ( ξ, X ) · S = 0, where C ̃, P, and H are quasiconformal, projective, and conharmonic curvature tensors.